BIOFILM ACCUMULATION IN DENTAL MATERIALS AND ITS REPERCUSSIONS ON ORAL HEALTH: CRITICAL REVIEW OF LITERATURE - Cavalcanti Barbosa, Allana Marcela; Rodrigues Acioli, Anny Caroline; Vasconcelos Cruz, Gabriela; Japiassú R. Montes, Marcos Antônio (Revista da Faculdade de Odontologia da Universidade Federal da Bahia, 2022)
Purpose: This article aims to conduct a literature review about the impact that biofilm accumulation on different types of dental materials can cause on oral health, according to its characteristics. Methods: Original articles about the accumulation of biofilm on the surface of different restorative and rehabilitative dental materials and their repercussions on oral health were gathered in journals in the PubMed and Lilacs databases using the search terms "Biofilm", "Dentistry", "Dental materials", through the logical operator "AND". An individual analysis of the articles that contemplated this study´s subject was performed. Results: As a result of the search, 439 articles were found, 416 from Pubmed and 23 from Lilacs, however only 23 studies (Pubmed: 20 and Lilacs: 3) were selected for content analysis. The majority of the selected articles discussed dental biofilm formation in the different restorative and rehabilitative dental materials and how their characteristics interfere in this accumulation. Final considerations: Bacterial adhesion and biofilm formation are strongly influenced by the surface characteristics of dental materials, such as their chemical compositions, surface roughness and surface free energy, what can lead to negative repercussions to the individual´s oral health.